2015
DOI: 10.1111/apt.13432
|View full text |Cite
|
Sign up to set email alerts
|

Miravirsen dosing in chronic hepatitis C patients results in decreased microRNA‐122 levels without affecting other microRNAs in plasma

Abstract: Summary Background MicroRNA‐122 (miR‐122) is an important host factor for hepatitis C virus replication. Administration of miravirsen, an anti‐miR‐122 oligonucleotide, resulted in a dose dependent and prolonged decrease in HCV RNA levels in chronic hepatitis C patients. Aim To assess the plasma level of various miRNAs in patients dosed with miravirsen. Methods We included 16 of 36 chronic hepatitis C patients who received five injections of either 3 mg/kg (n = 4), 5 mg/kg (n = 4), 7 mg/kg (n = 4) miravirsen or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(85 citation statements)
references
References 48 publications
0
80
0
Order By: Relevance
“…Although this fundamental work is essential and has significantly increased our understanding of the post-transcriptional regulation of FOXO3, research should now shift toward the in vivo regulation of FOXO3 targeting miRNAs in suitable animal models of human disease. Understanding how miRNAs regulate FOXO3 activity is of interest for many fields of biomedical research, as miRNAs potentially constitute novel and effective targets for human therapy 81 .…”
Section: Microrna-mediated Regulation Of Foxo3mentioning
confidence: 99%
“…Although this fundamental work is essential and has significantly increased our understanding of the post-transcriptional regulation of FOXO3, research should now shift toward the in vivo regulation of FOXO3 targeting miRNAs in suitable animal models of human disease. Understanding how miRNAs regulate FOXO3 activity is of interest for many fields of biomedical research, as miRNAs potentially constitute novel and effective targets for human therapy 81 .…”
Section: Microrna-mediated Regulation Of Foxo3mentioning
confidence: 99%
“…Dysfunctional miRNA expression, processing, and degradation have been found in breast cancer (Cammarata et al 2010), acute myeloid leukemia (Kobayashi et al 2014), ovarian cancer (Mulrane et al 2013), and hepatocellular carcinoma (Zhu et al 2011). Deregulated miRNA processing also contributes to other major diseases such as Hepatitis C (van der Ree et al 2016) and cardiovascular diseases (Small and Olson 2011). Because miRNAs regulate genes that change cellular fate, miRNAs and proteins involved in miRNA regulation are promising next-generation cancer therapeutic targets and specific components of the RNA processing machinery are current biomarkers for cancer detection (Barh et al 2010;Di Leva and Croce 2013;Fendler and Jung 2013;Zheng et al 2013;Moitra 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Pedersen et al further showed that the transfection of a miR-122 inhibitor into cells could suppress HCV replication with a similar magnitude of regulation to that induced by IFNβ alone (132). This and other findings have led to the development and in vivo testing of therapeutic miR-122 inhibitors that show promise for the treatment of chronic HCV infection (133, 134). …”
Section: Mir-122 Positively Regulates Cholesterol Facilitates Hcv Rementioning
confidence: 96%